THE IMPLEMENTATION OF VIRTUAL REALITY (VR) TECHNOLOGY IN REAL ESTATE INDUSTRY - Sahray, Kholim; Sukereman, Anis Syazwani; Rosman, Siti Hasniza; Jaafar, Nur Hanis (PLANNING MALAYSIA, 2023)
COVID-19 pandemic impact has accelerated the real estate industry to adopt technology evolution quickly. Due to the normalisation changes from the pandemic, all the physical real estate selling processes, including housing tours, sales, and purchase agreements, could not be effectively done as before. In this situation, Virtual Reality (VR) has become a prominent approach for real estate agents to improve their marketing strategies. This prospective study was designed to investigate the potential activities needed in VR implementation and to explore the importance of VR in influencing real estate marketing. Primary data was gathered from 60 real estate respondents using purposive sampling and descriptively analysed using SPSS software. The findings indicate that VR tours of the property, 360-degree visualisations, and visualisations of room furniture are the most potential activities needed in VR implementation. While VR is important because it indicates detailed information about the property, provides high-quality photos, and is a good investment opportunity. Overall, this study provides insights into how VR technology can help realtors survive in the evolving real estate industry.